Direct estimation of the spontaneous mutation rate by short‐term mutation accumulation lines in Chironomus riparius. Issue 2 (11th May 2017) - Oppold, Ann‐Marie; Pfenninger, Markus
Abstract : Mutations are the ultimate basis of evolution, yet their occurrence rate is known only for few species. We directly estimated the spontaneous mutation rate and the mutational spectrum in the nonbiting midge C. riparius with a new approach. Individuals from ten mutation accumulation lines over five generations were deep genome sequenced to count de novo mutations that were not present in a pool of F1 individuals, representing parental genotypes. We identified 51 new single site mutations of which 25 were insertions or deletions and 26 single nucleotide mutations. This shift in the mutational spectrum compared to other organisms was explained by the high A/T content of the species. We estimated a haploid mutation rate of 2.1 × 10 −9 (95% confidence interval: 1.4 × 10 −9 – 3.1 × 10 ‐9 ) that is in the range of recent estimates for other insects and supports the drift barrier hypothesis. We show that accurate mutation rate estimation from a high number of observed mutations is feasible with moderate effort even for nonmodel species.